Ecological Risk Assessment of Microplastics in Sediment and Bioaccumulation in Melanoides tuberculata Tissues in the Citarum River Downstream Area, Indonesia - Muhammad Rifal Khozin Azhary Rukmana; Nurul Chazanah; Fikri Ilmi; Sarah Mutiara Rahma; Nadya Timuria Cahyani (School of Postgraduate Studies, Diponegoro Univer, 2026)
Microplastic (MP) pollution has become a global concern in aquatic environments, particularly in rivers that serve as major pathways transporting pollutants to the ocean. As MPs consist of various polymer types with different toxicity levels, ecological risk assessment is essential to evaluate their potential impacts. This study assessed the ecological risk of MPs in riverbed sediments and their accumulation in the freshwater gastropod Melanoides tuberculata in the downstream Citarum River, an area prone to MP accumulation due to low flow velocity, high sedimentation rates, and increasing pollutant inputs from upstream. Sediment samples were analyzed to determine MP abundance and characteristics, while polymer types were identified using Fourier Transform Infrared (FTIR) spectroscopy. Ecological risk was evaluated using the Polymer Hazard Index (PHI), Pollution Load Index (PLI), and Potential Ecological Risk Index (PERI). The results showed high MP contamination in sediments, with a mean abundance of 63.37 ± 33.06 particles/100 g dry weight. The highest MP concentration and ecological risk were observed at site L3 (Tunggakjati). Identified polymers included polypropylene, polyethylene, and polyester. PHI indicated high to very high ecological risk, PLI revealed significant pollution loads, and PERI classified the sites as having high to very dangerous ecological risk. In M. tuberculata, the mean MP concentration was 3.47 ± 1.75 particles/g wet weight or 0.738 ± 0.14 particles per individual. Despite being located downstream of a dam, this section of the Citarum River remains an MP hotspot due to river confluences that concentrate upstream pollutants and enhance MP deposition in sediments and aquatic organisms. This study provides the first integrated ecological risk assessment combining sediment contamination and gastropod bioaccumulation in the downstream Citarum River, offering a scientific basis for microplastic pollution management.